OREOCALLIS GRANDIFLORA PHOTOPROTECTIVE EFFECT AGAINST ULTRAVIOLET B RADIATION-INDUCED CELL DEATH - D, Vinueza; D, Cajamarca; K, Acosta; G, Pilco (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this research was to evaluate the photoprotective effect of Oreocallis grandiflora hydroalcoholic extract (OGHE) against ultraviolet (UV)B-induced cell death model on a strain of Escherichia coli (ATCC 25922) and to determine the sun protection factor (SPF) using the equation proposed by Mansur. Methods: OGHE was obtained from leaves of O. grandiflora, following a standardized methodology. In short, O. grandiflora leaves were extracted with ethanol 70% v/v and defatted with n-hexane, hydroalcoholic fraction was concentrated under controlled conditions through rotary evaporator, and finally, the residue was freeze drying to obtain OGHE. The photoprotective effect was carried out using in vitro UVB-induced cell death model on a strain of E. coli (ATCC 25922), like a first approach to study its potential application on cosmetics. Results and Conclusions: From results, O. grandiflora is an important resource to produce new cosmetic products. However, the safety of OGHE is necessary to a rational development in that sense. OGHE shows advantages in relation to conventional active compounds of commercial sunscreens used in this research (2-ethylhexyl 4-methoxycinnamate and 2-ethylhexyl 4-(dimethylamino)benzoate) at the concentration of 2 mg/mL, on survivor time (with OGHE until 120 min), range of inactivation of E. coli caused by UVB (OGHE K value minor against to positive controls), and high SPF (13.56Â±0.21). Â 